2008
DOI: 10.1111/j.1463-1326.2008.00923.x
|View full text |Cite
|
Sign up to set email alerts
|

Glimepiride upregulates eNOS activity and inhibits cytokine‐induced NF‐κB activation through a phosphoinoside 3‐kinase–Akt‐dependent pathway

Abstract: These data suggest that glimepiride might be a preferable sulphonylurea agent in the setting of type 2 diabetes and vascular disease because it may have protective effects on vascular endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 20 publications
0
16
0
5
Order By: Relevance
“…[50][51][52][53] It would be interesting to determine whether glimepiride facilitates IPC by activating the PI3K-Akt pathway in the diabetic heart. In this regard, glimepiride has been reported to activate Akt in both coronary endothelial cells, 43 human umbilical vein endothelial cells, 44 and adipocytes. 45 Furthermore, it has been reported that the peroxisome proliferator-activated receptor (PPAR)-g agonist, rosiglitazone, also has the ability to cardioprotect the diabetic rat heart through the activation of Akt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[50][51][52][53] It would be interesting to determine whether glimepiride facilitates IPC by activating the PI3K-Akt pathway in the diabetic heart. In this regard, glimepiride has been reported to activate Akt in both coronary endothelial cells, 43 human umbilical vein endothelial cells, 44 and adipocytes. 45 Furthermore, it has been reported that the peroxisome proliferator-activated receptor (PPAR)-g agonist, rosiglitazone, also has the ability to cardioprotect the diabetic rat heart through the activation of Akt.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Importantly, the antidiabetic sulfonylurea, glibenclamide, which is used less frequently nowadays, is known to block the cardioprotective effects of IPC by acting as an antagonist of the mitochondrial ATP-dependent potassium channel. 40,41 Interestingly, the sulfonylurea, glimepiride, which does not block IPC cardioprotection, 42 has been reported to activate Akt when administered to the endothelial cells, 43 human umbilical vein endothelial cells, 44 and adipocytes. 45 In the present study, we investigate whether pretreatment with glimepiride can facilitate IPC in the diabetic heart.…”
Section: Introductionmentioning
confidence: 99%
“…Endothelin receptor type B ( EDNRB ) gene is located on 13q22, encoding a nonselective endothelin B receptor (ET B R) which belongs to a super-family of G-protein coupled receptor that mediates endothelins (ETs) [7]. ET B R is able to promote the production of neural crest cell-specific lineage, and thus it is related to the occurrence of Hirschsprung’s disease [8] that is a blockage in the colon.…”
Section: Introductionmentioning
confidence: 99%
“…Metformin and sulfonylurea drugs are popular anti-diabetic drugs that have been well described to reduce plasma glucose levels and improve circulating HDL and triglycerides [60]. Both classes of drugs are known to stimulate Akt phosphorylation and may therefore also block cellular autophagy [61,62]. This may suggest that augmentation of insulin receptor signaling and inhibition of cellular autophagy may positively affect both glucose and lipoprotein metabolism.…”
Section: Resultsmentioning
confidence: 99%